Perencanaan Ulang Jembatan Glapan Timur Kabupaten Grobogan Girder 40 Meter (Indonesian Journal of Civil Engineering Study, 2025)
East Glapan Bridge, Grobogan Regency is an alternative bridge that connects Gubug with Kedungjati, and Grobogan with Semarang City. Because the bridge building is quite old, it needs to be replaced with a new bridge that can function as an alternative route forward. In addition, several years ago, frequent flooding in the river basin had resulted in instability in the nine bridge pillars. In this research, the author used the superstructure of the bridge using prestressed concrete beams and the working load method, where the I girder was chosen as the main structural element. Bridge planning is carried out through manual structural analysis assisted by MS Excel software, with reference to SNI-1725-2016 which explains Loading for Bridges, apart from that also SNI-2833-2016 which discusses Bridge Planning against Earthquake Loads, as well as the latest PKJI (Indonesian Road Capacity Guidelines) from 2023, as well as relevant regulations regarding bridge planning. The results of the planning for the East Bridge, Grobogan Regency from the analysis of calculations that have been carried out, obtained 2 pillars and 2 types of girders with dimensions of 1,7 m and 2,1 m. The research results show that the bridge is declared safe and suitable for use, because the capacity value obtained from the calculation analysis exceeds the permit capacity value. Control of 2-way overturning, control of 2-way shear, control of lateral bearing capacity, control of 2-way axial bearing capacity, and control of the allowable bearing capacity of drilled piles showed good results. This analysis concludes that the condition of the planned bridge structure is safe to accept the combination of loads and ultimate loads.
Keywords: Planning; Bridge; Main structure